а)-2+3х=0
3х=2
х=2/3
б)4/11х=33
11/4×4/11х=11/4×33
х=363/4
в)8х-5=х-40
8х-х=40+5
7х=-35
х= -5
г)12=(6х+1)-(3х-2)
12=6х+1-3х+2
12=3х+3
-3х=3-12
-3х= -9
х=3
Объяснение:
3c-4d 3c+4d
( - )
4c-3d 4c+3d
12c^2 +9cd -16 cd -12d^2
(4c-3d ) ( 4c+3d) (по формуле (a+b) (a-b) =a^2 - b^2) 12c^2 -7 cd -12d^2 14 (4c-3d ) ( 4c+3d) : 4c+ 3d 12c^2 -7 cd -12d^2 (умножить на) 4c+3d (4c-3d ) ( 4c+3d) 14 (сокращаем) 12c^2 -7 cd -12d^2 4c^2-2cd 14 (4c-3d ) + 4c-3d (общий знаменатель 14 (4c-3d ). 4c-3d - домножим на 14) 12c^2 -7 cd -12d^2 +56с^2 -28cd =0 68c^2 -35cd -12d^2 =0 (под вечер мозг взорвался и был таков)
Подробнее - на -
а)-2+3х=0
3х=2
х=2/3
б)4/11х=33
11/4×4/11х=11/4×33
х=363/4
в)8х-5=х-40
8х-х=40+5
7х=-35
х= -5
г)12=(6х+1)-(3х-2)
12=6х+1-3х+2
12=3х+3
-3х=3-12
-3х= -9
х=3